(untitled) (Islamic Sciences Journal, 2023)
The jurisprudence rule is a majority judgment where the judgment over minor jurisprudence issues is directly identified. The jurisprudent standard is a majority judgment where the judgment over minor jurisprudence issues concerning an aspect of jurisprudence is directly identified. The fundamental rule means the total rules whereby judgments concerning its minor issues are identified. They are known as total issues whereby judgments can be deduced from their evidences from the holy Quran and Sunna in addition to other evidences. -The difference between the jurisprudence rule, the jurisprudence standard and fundamental rule is also identified. -Five jurisprudence rules have been identified and their applications are mentioned, as follows; the foundation does collocate with the substitute, judgment on speech is better than negating it, the worst of the loath something is better to beleft give away, injustice is abolished and does not need to be revoked.